Production and composition of peppermint essential oil in seasons after summer and winter transplantations - Souza, Jéssica Maronez de; Cargnelutti Filho, Alberto; Pezzini, Rafael Vieira; Somavilla, Felipe Manfio; Heinzmann, Berta Maria; Rodrigues, Patrícia (Comunicata Scientiae, 2024)
The aim of this study was to determine the season that provides the highest production and best quality of peppermint (Mentha x piperita L.) essential oil in summer and winter transplantations. Two experiments were performed in a protected cultivation, the first with transplantation in summer and the second with transplantation in winter, with a completely randomized design with four treatments, being the seasons of the year. Content, yield and chemical composition of the essential oil were determined. The essential oil was extracted by hydrodistillation and analyzed by gas chromatography. Essential oil content in summer and winter transplantations was higher in summer and essential oil yield was higher in spring. In the summer transplanting the major components were menthone, isomenthone and pulegone. In the winter transplanting menthone, menthofuran, isopulegone, pulegone and menthol were detected as major components. Menthofuran, a compound which reduces the essential oil quality, were found in high amounts in winter transplanted plants. The higher production of peppermint essential oil is obtained in summer and spring harvests and the main compound is menthone in all seasons. The best quality of essential oil is obtained in the summer transplanting.